The influence of in-cylinder flows and bulk gas density on early Spray G injection in an optical research engine. (January 2023) - Welch, Cooper; Schmidt, Marius; Geschwindner, Christopher; Wu, Shengqi; Wooldridge, Margaret S; Böhm, Benjamin
A well-characterized multi-hole gasoline injector, the Engine Combustion Network's (ECN) Spray G injector, was investigated in an optically accessible research engine under four motored operating conditions with early injection. The experiments were conducted at intake pressures of0 . 4 bar and0 . 95 bar, nearly matching the ECN's standard early injection operating conditions, Spray G2 (flash boiling) and Spray G3 (early injection), respectively. This was combined with two engine speeds at800 rpm and1500 rpm . Using particle image velocimetry and volumetric Mie scatter imaging, the in-cylinder flows were evaluated and the effects on the spray morphology were characterized. The in-cylinder flow was evaluated to understand the spray-flow interaction, including the turbulent kinetic energy. Little effect on turbulent energy was observed in the region examined near the exit of the fuel injector nozzle shortly after injection. Mie scatter imaging was used to characterize the spray morphology and wall wetting was clearly visible on the spark plug. Cyclic variability of the sprays was found to be insignificant; and major differences in spray morphology are attributed to the in-cylinder velocity and intake pressure at the time of injection. Decreasing the bulk gas density by decreasing the intake pressure had a number of effects on the evolution of the spray including faster evaporation, increased axial liquid penetration, and decreased spray angle. Increasing the in-cylinder flow magnitudes by increasing the engine speed had a similar effect on spray morphology by also increasing the evaporation rate, increasing the axial penetration, and decreasing the spray opening angle. Comparison of the motored spray cases with a no-flow case (when the fuel is sprayed into the engine without the piston present) further illustrated the extent to which the intake flow influenced the spray shape.